2023
DOI: 10.1038/s41380-023-02227-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cognitive effects of external trigeminal nerve stimulation (eTNS) in neurological and psychiatric disorders: a systematic review and meta-analysis

Samuel J. Westwood,
Aldo Alberto Conti,
Wanjie Tang
et al.

Abstract: This pre-registered (CRD42022322038) systematic review and meta-analysis investigated clinical and cognitive outcomes of external trigeminal nerve stimulation (eTNS) in neurological and psychiatric disorders. PubMed, OVID, Web of Science, Chinese National Knowledge Infrastructure, Wanfang, and VIP database for Chinese technical periodicals were searched (until 16/03/2022) to identify trials investigating cognitive and clinical outcomes of eTNS in neurological or psychiatric disorders. The Cochrane Risk of Bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 100 publications
(273 reference statements)
0
4
0
Order By: Relevance
“…Other non-pharmacological treatments such as behavioural therapies, cognitive training (CT) [ 38 ], Electrophysiology-Neurofeedback [ 3 ], non-invasive brain stimulation, fMRI Neurofeedback [ 27 , 29 ] or dietary interventions show only small to moderate efficacy on improving ADHD symptoms or cognition [ 3 – 5 ]. eTNS is hence the non-pharmacological treatment that has shown the largest effect size so far in improving ADHD and is the only non-pharmacological medical device licensed as treatment for ADHD by the FDA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other non-pharmacological treatments such as behavioural therapies, cognitive training (CT) [ 38 ], Electrophysiology-Neurofeedback [ 3 ], non-invasive brain stimulation, fMRI Neurofeedback [ 27 , 29 ] or dietary interventions show only small to moderate efficacy on improving ADHD symptoms or cognition [ 3 – 5 ]. eTNS is hence the non-pharmacological treatment that has shown the largest effect size so far in improving ADHD and is the only non-pharmacological medical device licensed as treatment for ADHD by the FDA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown improvements in pain, in neurological disorders such as epilepsy, migraine as well as in psychiatric disorders [ 38 ]. Our meta-analysis of TNS studies in neurological and psychiatric disorders showed improvement in migraine pain combined with medication and in depressive symptoms across three disorders [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations